Functional Literacy in the System of Adult Education - Olena Vasylenko (Jesuit University Ignatianum in Krakow, 2023)
RESEARCH OBJECTIVE: The scientific aim of the article is to improve understanding of func- tional literacy (illiteracy) phenomenon and its role in adult learning system, pedagogical and socio-economic approaches to this concept. THE RESEARCH PROBLEM AND METHODS: The research problem is included in the questions: What are the essence, definition and constituents of functional literacy? What are pedagogical principles and techniques of functional literacy training for adults? The author uses the method of theoretical analysis of scientific works, some documents and UNESCO reports on the issues, and comparison of certain research views. THE PROCESS OF ARGUMENTATION: The article starts with investigation of functional literacy in historical and contemporary dimensions, the reasons for development of the phenomenon in the world. Then we focus on various concepts and approaches to the functional literacy through the time. The next is comparison of scholars' research on the components of functional literacy; and then we study the principles and methods, peculiarities of functional literacy training in adult education. RESEARCH RESULTS: The research has revealed that functional literacy is a complex of social necessary knowledge and skills allowing a person to participate effectively in social process. Its constituent elements are basic, information, economic, political, cultural literacy, and many others depending on community level. Functional literacy concept and training are connected with the priorities of economic and social development. The constant interest by national and international organizations for maintaining functional literacy is explained in the work. CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: The conclusion emphasizes the importance of functional literacy for development and well-being of individual and societal progress in the community. The need for working out and implementation of specific principles, teaching materials and techniques for functional literacy training in adult learning is highlighted.